Comparing neuropathy in multiple myeloma and AL amyloidosis. Issue 1 (10th January 2021) - Ballegaard, Martin; Nelson, Lærke Marie; Gimsing, Peter
Abstract: Peripheral neuropathy (PN) is frequent in patients with monoclonal gammopathy due to plasma cell dyscrasia, but little is known about the comparative impact of nerve dysfunction in different disorders. We compared clinical and laboratory results between two diagnostic groups. We recruited 76 untreated multiple myeloma (MM) and 27 AL amyloidosis (ALA) patients for evaluation of symptoms, clinical findings and nerve conduction studies (NCS). We diagnosed significant PN using total neuropathy scores (TNS > 7) in 17.6% of MM and 48.1% of ALA patients and in 27.7% of MM and 35.7% of ALA patients using NCS findings. TNS score grades were significantly higher in the AL amyloidosis patients (Fisher's exact test: P = .02) but a NCS based PN diagnosis was not significantly different (Fisher's exact test: P = .13). A significantly higher TNS vibration ( P = .04) and pin ( P = .02) sensory sign and TNS reflex ( P = .04) sign score was found in amyloidosis patients. Likewise, quantitative sensory thresholds for vibration was higher in amyloidosis patients (Welsh ANOVA: P = .01). NCS revealed signs of more frequent axonal tibial neuropathy with significantly lower motor response amplitudes ( P = .02) and resulting higher TNS scores ( P = .002), while sural nerve sensory response amplitudes were without significant difference ( P = .86). We found more severe TNS grades of PN in AL amyloidosis patients compared with MM patients. We also found higher sensory symptoms scores and higher thresholds for vibration but similar sensory involvement using NCS. The NCS exclusively showed signs of an axonal neuropathy.